(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
This research examines the statistical method for quality control. The accuracy of parts is controlled statistical evaluation - an average and a dispersion of the indicator for accuracy. This paper reports a method for quality control of parts of average indicators and algorithm for quality control of the average and dispersion of samples of small size. It proposes a criterion of applicability of statistical adjustment of accuracy by sampling for control of the average data of the quality indicator. It proves the influence of the dispersion of the quality indicator for impairing the quality of the process.